Electrodeposited Nickel Cobalt Sulfide Flowerlike Architectures on Disposable Cellulose Filter Paper for Enzyme-Free Glucose Sensor Applications - Babu, Kaliyamoorthy Justice; Raj Kumar, T.; Yoo, Dong Jin; Phang, Siew Moi; Kumar, Georgepeter Gnana (American Chemical Society, 2018)
Three-dimensional flowerlike nickel cobalt sulfide (NiCo2S4) nanostructures are electrochemically deposited over the Ni-modified cellulose filter paper (CFP). The fabricated NiCo2S4/Ni/CFP is explored as a binder-free and self-standing electrode for enzyme-free electrochemical detection of glucose in alkaline media, in which Ni/CFP and NiCo2S4 serve as the current collector and active material, respectively. Owing to the rich redox active sites, synergistic effect between Co4+ and Ni3+, and rapid electron transportation tuned with the substitution of sulfur (S) with oxygen labile functional group, NiCo2S4/Ni/CFP exhibits considerable enzyme-free glucose-sensing performance with wide linear glucose concentration ranging from 0.5 μM to 6 mM, high sensitivity of 283 μA mM-1 cm-2, and low detection limit of 50 nM. The developed NiCo2S4/Ni/CFP's sensing performances are reproducible, stable, and highly selective toward the analyte of interest in physiological interfering species. Thus, the self-standing, binder-free, inexpensive, easily disposable, and facile electrode fabrication process proposed in this study opens a new paradigm architecture for the development of efficient electrochemical sensor devices with affordable cost.